Sekolah Penggerak : Does Curriculum Design Made Fit with the Program? - Mulyadi, Didi; Mardiana, Rita (Adpebi International Journal of Multidisciplinary Sciences, 2022)
The Program Sekolah Penggerak is a transformation of the Education program to realize Pancasila students based on holistic student learning outcomes. To achieve this program, this program is supported by an independent curriculum where teachers are expected to provide more holistic. This research is aimed at seeing how the curriculum in this program is structured as well as targets for each stage. This research uses pure qualitative research by using literature and docuseries (literary research). The results of this study explain that there are several stages in the concept of independent learning, namely the planning stage and also the implementation stage where each stage has specific targets along with achievements based on the competence of students. From the results found, the concept of this independent learning curriculum has detailly described the achievements of each stage and how teachers implement them in the classroom. Given that Indonesia is so diverse, the implementation of this independent curriculum requires periodic and detailed evaluation of each region.